WORKLOAD ANALYSIS OF EMPLOYEES IN THE IMPLEMENTATION OF TASKS IN THE ENVIRONMENTAND FORESTRY DEPARTMENT OF BOALEMO DISTRICT - fandriyanto lahay; Imam Mashudi; Maman Musa (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to analyze the workload of employees in carrying out their duties at the Boalemo District Environment and Forestry Service. The method in this study uses descriptive qualitative methods with data collection techniques, observations, interviews, documentation and uses data analysis, namely data reduction (data reduction), data display (data presentation), conclusion drawing / verification. The results of this study indicate that the lack of employees in the field of personnel causes the workload to not balance between the fields in the Department of Environment and Forestry, Boalemo Regency. This also has an impact on the physical burden, mental burden, and time burden where the time burden is heavier or more dominant than the physical and mental burden.